Initial Guidance on Use of Monoclonal Antibody Therapy for Treatment of Coronavirus Disease 2019 in Children and Adolescents. (3rd January 2021) - Wolf, Joshua; Abzug, Mark J; Wattier, Rachel L; Sue, Paul K; Vora, Surabhi B; Zachariah, Philip; Dulek, Daniel E; Waghmare, Alpana; Olivero, Rosemary; Downes, Kevin J; James, Scott H; Pinninti, Swetha G; et al.
Abstract : Although monoclonal antibody therapies for coronavirus disease 2019 have received emergency use authorization for treatment of adolescents in specified high-risk categories, there is currently insufficient evidence for necessity, safety, or efficacy to recommend routine use, even in those with specified conditions. Abstract: Background: In November 2020, the US Food and Drug Administration (FDA) provided Emergency Use Authorizations (EUA) for 2 novel virus-neutralizing monoclonal antibody therapies, bamlanivimab and REGN-COV2 (casirivimab plus imdevimab), for the treatment of mild to moderate coronavirus disease 2019 (COVID-19) in adolescents and adults in specified high-risk groups. This has challenged clinicians to determine the best approach to use of these products. Methods: A panel of experts in pediatric infectious diseases, pediatric infectious diseases pharmacy, pediatric intensive care medicine, and pediatric hematology from 29 geographically diverse North American institutions was convened. Through a series of teleconferences and web-based surveys, a guidance statement was developed and refined based on review of the best available evidence and expert opinion. Results: The course of COVID-19 in children and adolescents is typically mild and there is no high-quality evidence supporting any high-risk groups. There is no evidence for safety and efficacy of monoclonal antibody therapy for treatment of COVID-19 in children or adolescents, limited evidence of modest benefit in adults, and evidence for potential harm associated with infusion reactions or anaphylaxis. Conclusions: Based on evidence available as of December 20, 2020, the panel suggests against routine administration of monoclonal antibody therapy (bamlanivimab, or casirivimab and imdevimab), for treatment of COVID-19 in children or adolescents, including those designated by the FDA as at high risk of progression to hospitalization or severe disease. Clinicians and health systems choosing to use these agents on an individualized basis should consider risk factors supported by pediatric-specific evidence and ensure the implementation of a system for safe and timely administration that does not exacerbate existing healthcare disparities.